2008
DOI: 10.3390/medicina44090086
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of reticulocyte hemoglobin content to diagnose iron deficiency in 6–24-month-old children

Abstract: Objective. The aim of our study was to evaluate the prognostic value of reticulocyte hemoglobin content for diagnosis of iron deficiency in 6-24-month-old children.Material and methods. Children aged 6 to 24 months were consulted for suspected iron deficiency in the outpatient department in 2006-2007. Criteria for inclusion into the study were normal birth time and weight, no infection during the last two weeks before blood sampling (Creactive protein <5 mg/L), no iron supplements 1 month before the study. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
1
11
0
3
Order By: Relevance
“…Our observed lower reference levels (-2 SD) at 4 and 12 months of 25.6 and 24.9 pg/L respectively, corresponds well to the cut off level of 25 pg/L commonly used to diagnose ID in older children (33). Ret-He or its equivalent CHr has shown promise in the identification of children with ID solely on the basis of hematological parameters, (11) as well as a potential predictive tool as an early indicator of ID in infants (12,13) even though its use as a single biomarker has been challenged (9) In our correlation analysis, Ret-He was strongly correlated to sTfR at all ages, while there were varying correlations to MCV, Ferritin and TS as well as Hb. This might reflect that these indicators describe different stages of iron metabolism.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our observed lower reference levels (-2 SD) at 4 and 12 months of 25.6 and 24.9 pg/L respectively, corresponds well to the cut off level of 25 pg/L commonly used to diagnose ID in older children (33). Ret-He or its equivalent CHr has shown promise in the identification of children with ID solely on the basis of hematological parameters, (11) as well as a potential predictive tool as an early indicator of ID in infants (12,13) even though its use as a single biomarker has been challenged (9) In our correlation analysis, Ret-He was strongly correlated to sTfR at all ages, while there were varying correlations to MCV, Ferritin and TS as well as Hb. This might reflect that these indicators describe different stages of iron metabolism.…”
Section: Discussionsupporting
confidence: 59%
“…In this setting, reticulocyte hemoglobin content (Ret-He) has emerged as a relatively new iron status marker. In some previous studies, it has even shown promising qualities as a biomarker of early ID (11,12). Two methods for analysis of Ret-He are available; the CHr (mean cellular hemoglobin content of reticulocytes) parameter provided by the ADVIA 120 and 2120 (Bayer Diagnostics, Tarrytown, NY) and the Ret-He (reticulocyte hemoglobin equivalent) available on analyzers from the Sysmex Corporation, Kobe, Japan (XE 2100, XE 5000 and the XN series), respectively, and show very good level agreement (13).…”
Section: Introductionmentioning
confidence: 99%
“…All 3 performed well, but it should be noted that the study controlled at least partially for inflammation as it excluded children with recent infection or CRP greater than 5 mg/L. 45 Another study of 237 children found that RHC was the most accurate marker for iron deficiency, a cutoff value 25 pg providing a sensitivity of 94% and specificity of 80%. 46 RHC has also been used to assess iron status in patients on hemodialysis, where measurements of ferritin and transferrin saturation can be unreliable.…”
Section: Ferritin Is Prone To False-negative Results In Some Patient mentioning
confidence: 98%
“…Penelusuran abstrak dan judul. 16 juga memiliki nilai sensitivitas dan spesifisitas yang hampir sama meskipun usia subyek dalam studi ini sangat bebeda, akan tetapi nilai batas RET-He yang digunakan hampir serupa yaitu ≤ 29 pg dan ≤ 28,55 pg.…”
Section: Masalah Klinisunclassified
“…Sensitivitas dan spesifisitas RET-He dengan nilai batas ≤ 27,5 pg pada usia 9-12 bulan sebesar 83% dan 72%. 10 Nilai ini hampir serupa dengan nilai sensitivitas dan spesifisitas dalam 3 studi yang ditelaah diatas, kecuali studi Kiudelienė dkk, 16 memiliki sensitivitas dan spesifisitas lebih rendah karena menggunakan nilai batas RET-He yang lebih tinggi yaitu ≤28,55 pg.…”
Section: Metodeunclassified